Imaging solids using full waveform inversion - Kucukcoban, Sezgin; Goh, Heedong; Kallivokas, Loukas (The Journal of the Acoustical Society of America, 2021)
Wave-driven approaches have long been dominant in the nondestructive evaluation of both engineered and natural systems. In this presentation, we discuss recent progress in the full-waveform inversion (FWI) approach for the material characterization and condition assessment of solids probed by elastic waves. In FWI, characterization and localization of defects is automatically revealed once the distribution of the spatially-varying material properties is completed. In this work, we seek to image the Lamé parameters of arbitrarily heterogeneous solids, when probed by elastic waves in the time domain. Accordingly, we use the apparatus of PDE-constrained optimization and seek the Lamé parameter distributions that minimize the misfit between measured and computed responses, subject to the governing PDEs. As is commonly the case, the resulting inverted profiles of the second Lamé parameter (μ) are of better quality than those of the first (λ). To improve the resolution of both Lamé parameters, we discuss the use of three robustifying schemes, namely, source-frequency continuation, regularization factor continuation, and a search direction-biasing scheme. We demonstrate with numerical experiments the effect the schemes have on the inversion process and conclude with an application of the robustified full-waveform method to a challenging adaptation of the benchmark Marmousi2 model.